2019
DOI: 10.15640/jpbs.v7n2a7
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Burnout through a Mindful Meditation Mobile App: A Randomized Controlled Trial

Abstract: Given recent findings on the positive effects of mindful meditation interventions, exploring its benefits through new delivery mediums is valuable. The purpose of this study was to explore the effects of a mindful meditation intervention on burnout and mood using a mobile app (Smiling Mind) in 105 working adults in the United States. Mobile apps allow for standardized delivery in busy populations at a low cost and high convenience. Interventions can be conducted over the internet with no requirement of travel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…According to the findings of this study, online intervention is effective at reducing job-burnout, confirming the findings of Jonas et al [ 39 ] who found that online intervention helped participants reduce their symptoms of burnout. This study’s findings agree with those of Lanz et al [ 40 ] who found a significant decrease in burnout levels of participants in the intervention group using an online intervention. Other related Nigerian studies showed that blended REBT which involved online and face-to-face interventions was efficacious in reducing stress.…”
Section: Discussionsupporting
confidence: 92%
“…According to the findings of this study, online intervention is effective at reducing job-burnout, confirming the findings of Jonas et al [ 39 ] who found that online intervention helped participants reduce their symptoms of burnout. This study’s findings agree with those of Lanz et al [ 40 ] who found a significant decrease in burnout levels of participants in the intervention group using an online intervention. Other related Nigerian studies showed that blended REBT which involved online and face-to-face interventions was efficacious in reducing stress.…”
Section: Discussionsupporting
confidence: 92%
“…The studies all showed that the use of Calm or Smiling Mind resulted in some positive improvements in mental health. Statistically significant reductions were demonstrated in symptoms of stress (Huberty et al, 2019c), anxiety (Puzia et al, 2020a) and burnout (Callender et al, 2021; Lanz et al, 2019). One study with obstetric and gynaecology patients found that 93% of participants perceived a reduction in stress levels after a 30-day meditation intervention using Calm (Smith et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, emergency nurses must make decisions for patients in acute situations, deal with a wide range of illnesses and injuries, and operate professionally, alertly, and flexibly in life-threatening situations while dealing with constant distractions or interruptions. Many mindfulness-based interventions for health professionals have been implemented, mainly in the USA [ 9 , 10 , 11 , 12 , 13 ], Brazil [ 14 ], Australia [ 15 ], Japan [ 16 ], Thailand [ 17 ], Malaysia [ 18 ], and Taiwan [ 19 ]. However, there is less data in Europe; for instance, some programs have been implemented in the UK [ 20 ] and Spain [ 21 ].…”
Section: Introductionmentioning
confidence: 99%